CAM-SERAMİK SÜPERİLETKENLERİN BAZI TEMEL ÖZELLİKLERİNİN İNCELENMESİ - KORALAY, HALUK (Fırat Üniveristesi, 1997)
Bu çalışmada, Bİ2Sr2CaCu30x (2:2:1:3) başlangıç kompozisyonu hızlı katılaştırma yöntemi kullanılarak hazırlandı. Elde edilen numunelerin ısıl işlemlerden önceki ve sonraki mikroyapıları, fiziksel özellikleri; DTA, DSC, TGA, SEM, XRD ve direnç ölçümü metotlarıyla belirlendi. DTA analizinden, 2213 numunesinin kristalleşme sıcaklığı (Tx ) 450.9°C, erime sıcaklığı (Tm ) ise 860.0°C olarak bulundu. Numunenin optimum tavlama sıcaklığı 830°C olarak belirlendi. DSC eğrilerinden aktivasyon enerjisi 348.14 KJ/mol olarak hesaplandı. Numunenin n=l ve n=2 fazına sahip olduğu tespit edildi. Süperiletken geçiş sıcaklığı 68K olarak bulundu. Anahtar kelimeler: Süperiletkenlik, BSCCO sistemi, 2:2:1:3, Termal analiz, Aktivasyon enerjisi

In this study, Bİ2Sr2CaCu30x (2:2: 1 :3) nominal composition have been prepared by using melt-quenching method. The resulting samples' physical properties and their microstructures before and after heat treatment have been determined by DTA, DSC, TGA, SEM, XRD and resistivity measurement methods. By DTA analysis, the crystallisation temperature (Tx) and melting temperature (Tm) of 2:2:1:3 sample are found to be 450.9°C and 860.0°C, respectively. The optimum annealing temperature is determined to be 830.0°C. The activation energy is calculated from DSC curves and it was found to be 348.14 KJ/mol. It is also determined that the sample contains the n=l and n=2 phases. The superconductivity properties for the samples have been obtained at 68K temperature. Key Words: Superconductivity, BSCCO system, 2:2:1:3, Thermal analysis, Activation energy
An investigation on some fundamental properties of glass-ceramic superconductors
Keywords: Fizik ve Fizik Mühendisliği; Physics and Physics Engineering